ANALISIS PEMANFAATAN ARTIFICIAL INTELLIGENCE (AI) DALAM EFISIENSI PEMBUATAN KONTEN DIGITAL PADA APLIKASI TIKTOK - Agnes Monica; Vionetha Lavega; Vivian Vivian; Dorie Pandora Kesuma (Jurnal Riset Sistem Informasi, 2026)
The development of digital technology has encouraged the utilization of Artificial Intelligence (AI) in various activities, including digital content creation on social media platforms such as TikTok. This study aims to analyze the role of AI in improving the efficiency of digital content creation on the TikTok application. The research employed a qualitative method with a literature review approach by examining various relevant scientific sources, including journals, books, articles, and previous studies. The results indicate that the utilization of AI contributes to improving the efficiency of the content creation process through the automation of various production stages, enhancement of content quality, and optimization of audience interaction. In addition to increasing productivity, AI also helps content creators produce content that is more relevant and adaptive to digital trends. However, the utilization of AI still faces several challenges, such as algorithmic bias, dependence on automated systems, and the risk of reduced content originality. Therefore, the use of AI should be balanced with users' creativity and capabilities to maximize the benefits of the technology. This study shows that AI plays a strategic role as a supporting technology in improving the efficiency and effectiveness of digital content creation on the TikTok platform.